The Influence of Nursing Organizational Culture and Job Stress On Turnover Intention With Nurses' Commitment In Intervening Variables In Hospitals - Taniatun Nafiah; Iin Anisah; Noveria Susijawati (Journal Research of Social Science, Economics, and Management, 2024)
Turnover Intention is an interesting topic to discuss in a company because moving employees will disrupt company operations both in terms of cost and time. This study was conducted to determine the influence of nursing organizational culture and work stress on turnover intention with nurse commitment as an intervening variable in hospitals. The population in this study was employees in the hospital totaling 421 people with the number of nurses who were a population sample of 150 people. This study used quantitative methods with data collection through the distribution of questionnaires to hospital nurses. These findings provide important insights for hospitals and communities in understanding the factors that influence turnover intention.